Eric Drummond and his Legacies The League of Nations and the Beginnings of Global Governance - Macfadyen, David; Davies, Michael D. V.; Carr, Marilyn Norah; Burley, John (Understanding Governance, 2019)
XXIX, 361 p. 17 illus., 8 illus. in color.